Kelly, Kim. Photograph of Phillip O'Brien, Reggie Carew, Sheila Kelly, and others performing music. - Heritage NL
Kim Kelly provided a picture of Phillip O'Brien, Reggie Carew, Sheila Kelly, and others during a musical performance. Three men are on guitar, one man is playing an accordion, and Sheila is dancing.